Schauplätze und Themen der Umweltgeschichte - Umwelthistorische Miszellen aus dem Graduiertenkolleg ; Werkstattbericht - Herrmann, Bernd; Stobbe, Urte (Universitätsverlag Göttingen, 2009)
"Scenes and Topics of the History of Ecology" is the third workshop report presenting selected places of importance for the history of ecology, that can be recommended as travel destinations. Some topics could be attributed to a certain location only with great difficulties - if at all. For others there may be imaginary associations only. Therefore some essays and papers do not strictly adhere to the original intention. The volume continues the reports from the seminars, which are also intended to give outside observers a chance to stress their ecological consciousness. The reports may also serve as discussion material for similar seminars.